Analisis Pemilihan Moda Bus dan Kereta Api Rute Malang-Jakarta Menggunakan Metode Stated Preference - Marselinus Weleng; Galih Damar Pandulu; Pamela Dinar Rahma (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Transportation services connecting major cities play a vital role in facilitating public mobility, particularly along the Malang–Jakarta route, which has a high passenger volume. The two main options available are bus services and executive trains, both of which offer comparative advantages in terms of travel time, fares, and accessibility. This study is designed to explore the user profiles of these two modes, identify the determinants shaping mode choice preferences, and develop a mathematical model for predicting mode choice along the Malang–Jakarta corridor. The research approach adopts the stated preference technique, with data collected directly through a survey distributed to 100 bus users and 100 train users. The evaluated parameters include fare variations, differences in travel time, time differences to reach the terminal or station, and variations in departure schedules. The applied analytical techniques are multiple regression and the binomial logit model. The findings indicate that fare and accessibility factors have a dominant impact compared to other variables in determining mode choice. The resulting prediction model is capable of describing fluctuations in the probability of use between buses and trains in response to changes in service attributes. This research is expected to provide practical insights for transportation operators and policymakers in optimizing service standards and designing more efficient intercity transportation systems.